Determinants of birth registration in sub-Saharan Africa: evidence from demographic and health surveys - Aboagye, Richard Gyan; Okyere, Joshua; Seidu, Abdul-Aziz; Ahinkorah, Bright Opoku; Budu, Eugene; Yaya, Sanni (Frontiers in Public Health, 2023)
Background: Birth registration is a crucial aspect of ensuring that children have access to their rights and benefits, including health care, education, and citizenship. In sub-Saharan Africa (SSA), birth registration rates remain low, with millions of children going unregistered each year. Understanding the predictors of birth registration among children in this sub-region is important for developing targeted interventions to improve registration rates. The study examines the predictors of birth registration among children in SSA.Methods: We performed a cross-sectional analysis of secondary data pooled from the Demographic and Health Survey (DHS) of seventeen (17) countries conducted from 2015 to 2021. A weighted sample of 162,500 children with completed observations on all variables of interest was included in the final analysis. We summarised the proportion of birth registration among the children in SSA using a forest plot. We utilised a multilevel binary logistic regression analysis to examine the predictors of birth registration. The results were presented using adjusted odds ratios (aOR) with 95% confidence intervals (CIs).We found that 48.32% [48.15-48.49) of births in SSA were registered. The lowest and highest prevalence of birth registration were found in Ethiopia (2.70 [2.38-3.02]) and Sierra .50]), respectively. Increasing child age was found to be significantly associated with a higher likelihood of birth registrations, with those aged 4 years [aOR=1.55; CI=1.49, 1.62] having the highest odds of birth registration compared to at aged below 1 year. Children born to mothers with primary [aOR=1.17; CI=1.11, 1.24], secondary [aOR=1.44; CI=1.34, 1.54], or higher education [aOR=1.71; CI=1.48, 1.99] were more likely to be registered than those born to mothers who have no formal education. Also, children born in health facilities were more likely to have been registered [aOR=1.60; CI=1.48, 1.74] than those born at home. The odds of birth registration was significantly higher among children whose mothers received assistance during delivery [aOR=1.88; CI=1.72, 2.04], those in the richest wealth index [aOR=3.91; CI=3.54, 4.33], and those in rural areas [aOR=1.92; CI=1.76, 2.10].